Features of the formation of the territorial type of a sense of patriotism - S. N. Kipreev (Вестник Северо-Кавказского федерального университета)
This article discusses the typological features of the study of the feeling of patriotism among cadets conducted in educational organizations of the Ministry of Internal Affairs of Russia. The specifics of the educational process and the organization of interaction between an educational institution and public organizations in the formation of patriotism are revealed. The features of the territorial type of the feeling of patriotism are described: the concept, types, research, specifics of education. The author of the article actualizes the understanding of the Small Motherland as an object of patriotic feelings. The results of the study are valuable for the prevention of separatism, extreme nationalism, and ethno-confessional intolerance. The description of promising directions for further research on the topic of fostering a territorial sense of patriotism is given. The purpose of this study is to describe the specifics of the formation of the territorial type of a sense of patriotism. The objectives of the study were to describe the features of the relationship of the territorial sense of patriotism with its other types, which shows the significance of the studied manifestation of the type of feeling of love for the Motherland; consideration of the classification of Russian citizens according to the territorial perception of patriotism; coverage of the history of research on the territorial type of the sense of patriotism. To collect and analyze the research data, we used the analysis of literary sources, semantic analysis, sociological survey, generalization of empirical data from other researchers. The main results of the study were the enrichment of pedagogical science by concretization of the understanding of the significance of the process of formation of regional patriotism, the identification of a number of problems that have a significant impact on the development of territorial sense of patriotism. The work has an undoubted novelty due to the fact that in the conditions of the complicated foreign policy situation in the modern world, it allows us to better understand the processes of unity of the peoples of Russia on the basis of patriotic feelings.